ANALYSIS OF INFORMATION TECHNOLOGY RISK MANAGEMENT IN RAJA COMPUTER BALIKPAPAN BRANCH USING ISO 31000 FRAMEWORK - Ilda; Auliyah, Rezvina (CV RIFAINSTITUT, 2021)
Raja Computer Balikpapan Branch is a store that is engaged in selling computers, the store already uses IS/IT in supporting every business activity it carries out. The store uses the Ipost application which is used to support computer sales, record stock of goods, and can be used to record daily contests needed by the store. However, in the world of management, there is always the possibility of risks that may occur and can interfere with business activities in using the system. Thus, an analysis is needed of the IS/IT resources contained in the computer shop. Therefore, it is hoped that using ISO 31000 can help minimize every risk contained in the Ipost application. The results of this risk analysis are in the form of an analysis of possible risks, can group possible risks based on applications that can generate offers and risks that exist in Ipost, so the computer shop can treat existing risks according to the priority level of risk and be able to prevent and minimize disrupting business activities at Raja Computer store Balikpapan branch.